2020
DOI: 10.3389/fvets.2020.580523
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Predictability and Controllability on Stress Responses to the Aversive Component of a Virtual Fence

Abstract: To ensure animal welfare is not compromised, virtual fencing must be predictable and controllable, and this is achieved through associative learning. To assess the influence of predictability and controllability on physiological and behavioral responses to the aversive component of a virtual fence, two methods of training animals were compared. In the first method, positive punishment training involved sheep learning that after an audio stimulus, an electrical stimulus would follow only when they did not respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…To demonstrate this, plasma cortisol and β-endorphin concentrations were assessed in beef cattle receiving an electrical pulse compared with a range of common husbandry procedures and this showed that the stress response to an electrical pulse was not different to being restrained in a crush ( 17 ). In a similar comparison study with sheep, a mild cortisol response to an electrical pulse was shown and this was similar to hearing a barking dog ( 18 ) and sheep did not differ in their cortisol responses to the audio cue once they had successfully learnt the virtual fence ( 24 ). Overall, these results indicate that while the electrical pulse is aversive, it is not more stressful than common handling procedures in both sheep and cattle.…”
Section: Physiological Indicators Of Stressmentioning
confidence: 70%
See 1 more Smart Citation
“…To demonstrate this, plasma cortisol and β-endorphin concentrations were assessed in beef cattle receiving an electrical pulse compared with a range of common husbandry procedures and this showed that the stress response to an electrical pulse was not different to being restrained in a crush ( 17 ). In a similar comparison study with sheep, a mild cortisol response to an electrical pulse was shown and this was similar to hearing a barking dog ( 18 ) and sheep did not differ in their cortisol responses to the audio cue once they had successfully learnt the virtual fence ( 24 ). Overall, these results indicate that while the electrical pulse is aversive, it is not more stressful than common handling procedures in both sheep and cattle.…”
Section: Physiological Indicators Of Stressmentioning
confidence: 70%
“…Indeed, cattle learn rapidly after an average of 2.5 interactions with the virtual fence before responding to the audio cue alone ( 6 ). This hypothesis was tested Kearton et al ( 24 ) in a study that assessed the influence of controllability on stress responses to virtual fencing stimuli. Sheep that had learned to predict and control receiving the electrical pulse through their behavioral responses, did not differ in their cortisol, core body temperature and behavioral responses compared with a control treatment that did not receive any cues.…”
Section: Cognitive Measures Of Welfarementioning
confidence: 99%
“…The result indicated that subjective uncontrollability was associated with stress-induced HPA axis activation. Many animal studies have found that objective uncontrollability could affect neurobiology after stress, manifested as elevated cortisol levels (e.g., Davis et al, 1977;Dess et al, 1983;Kearton et al, 2020). However, other studies found that control is not correlated with HPA axis responses when manipulating actual control over a stressor in rodents (e.g., Maier et al, 1986;Weinberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Controllability is one factor that may influence the HPA axis response to stress (Dickerson and Kemeny, 2004). Many animal studies demonstrated that lack or loss of actual control was associated with HPA axis stress response (e.g., Davis et al, 1977;Dess et al, 1983;Kearton et al, 2020). For example, sheep receiving predictable but uncontrollable aversive stimulus had a higher cortisol compared to the control group (Kearton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation